Comparison of Cutinase Separation in Different Chromatographic Media - Abdul Wahab Mohammad; Jamaliah Md. Jahim; Suhalia Johar; Osman Hasan (ASEAN Journal of Chemical Engineering, 2012)
Cutinase is a hydrolytic enzyme that has both properties of lipase and esterase, thus finding its use in many areas. Previous studies have investigated both upstream and downstream processes for cutinase production from microbial source. However, no study has yet to address the use of membrane chromatography for cutinase purification, which is more favourable in terms of process resolution and product throughput as compared to the conventional gel chromatography. Hydrophobic interaction was chosen as the separation mechanism for cutinase purification in this study. The optimisation of cutinase purification in two different types of chromatographic media; conventional packed-gel and membrane matrix, were pre-determined by the best compromise between the recovery and purity of the purified cutinase. It was found that the optimised condition were of pH 4.0 and 1.0 M ammonium sulfate for the conventional column (50% recovery, 4.8-fold purity) and pH 6.0 with 1.5 M ammonium sulfate for the membrane–matrix column(87% recovery, 30-fold purity). Preferential interaction analysis was used to describe the protein chromatographic behaviour in each chromatographic media. Graph of natural algorithm of protein retention data to the function of salt concentration at pH 4.0 and 6.0 for each column were plotted. It was found that at the optimum pH condition for gel-packed column, a small amount of ammonium sulfate was sufficient to achieve maximum cutinase recovery and purity since the effect of salt at that particular pH were less significant. Consequently, the number of released water molecules were calculated and it was observed that for membrane column, larger number of water was released at pH 6.0 illustrating more protein were bounded to the stationary phase, thus explaining the optimum pH condition of the particular column.